Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan - Fauziah Rahman; Resky Rahmana; Husnul Khatimah B; Agus Halim (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
The physical work environment plays a strategic role in supporting employee performance, particularly in the manufacturing industry, which requires accuracy, speed, and physical endurance in daily operations. Inadequate physical work conditions, such as insufficient lighting, uncomfortable room temperature, high noise levels, and non-ergonomic workspace layout, can reduce employee concentration and productivity. This study aims to examine the effect of the physical work environment on employee performance in the manufacturing sector. A quantitative approach was employed using a survey method by distributing questionnaires to employees. Data analysis was conducted using statistical techniques to test the influence of the physical work environment on employee performance. The findings reveal that the physical work environment has a significant effect on employee performance. A conducive work environment can improve work effectiveness, minimize errors, and encourage employees to achieve optimal performance. Therefore, manufacturing companies should prioritize the management of physical work environment conditions to enhance sustainable employee performance.